2017
DOI: 10.1136/emermed-2017-206663
|View full text |Cite
|
Sign up to set email alerts
|

Emergency versus standard response: time efficacy of London’s Air Ambulance rapid response vehicle

Abstract: The current study found RRVs to be significantly quicker when responding with lights, sirens and traffic rule exemptions compared with a response being compliant with all traffic signals, road signs and speed limits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
0
13
0
1
Order By: Relevance
“…Rehn and colleagues have demonstrated that typical traffic conditions result in substantially slower transport to hospital 4. We have found that the online controlling of traffic lights is a feasible system that can decrease ambulance drive times to hospitals.…”
mentioning
confidence: 80%
“…Rehn and colleagues have demonstrated that typical traffic conditions result in substantially slower transport to hospital 4. We have found that the online controlling of traffic lights is a feasible system that can decrease ambulance drive times to hospitals.…”
mentioning
confidence: 80%
“…The first responders’ arrival time varies around the world and is influenced by geographical isolation. Countries with a developed ambulance service report a response time of less than 15 min [[9], [10], [11]]. Time from ambulance response to hospital admission is also an important consideration when trying to replicate a real-world scenario.…”
Section: Methods Detailsmentioning
confidence: 99%
“…Insignificant variables were dropped during the model estimations. The ambulance drivers, usually violating the traffic rule for the sake of time constraints [25], determined the severity of the injury the most. It appeared that male drivers or injured ambulance drivers were involved more in crashes with the worse injuries.…”
Section: Ol Regression Modelmentioning
confidence: 99%